Pengaruh Strategi Pembelajaran Metakognitif dan Gaya Kognitif Terhadap Kemampuan Pemecahan Masalah Matematika Siswa (Exsperimen pada Madrasah Tsanawiyah Kecamatan Wanasaba Lombok Timur) - Hasbullah -; Hartati Muchtar; Basuki Wibawa (JTP - Jurnal Teknologi Pendidikan, 2017)
The aim of this research was to determine the effect of metacognitive instructional strategy and cognitive style on students’ mathematics problem solving ability in the seventh grade of Madrasah Tsanawiyah, Wanasaba district. The research method used a quasi-experimental with 3 x 2 ANOVA factorial design. The results indicate that: (1) students’ ability on mathematics problem solving who uses IDEAL metacognitive instructional strategy is higher than who uses KWL and learning portfolio. (2) the ability on mathematics problem solving of students with field independent cognitive style is higher than field dependent cognitive style. (3) There is an interaction effect between metacognitive instructional strategy and cognitive style on mathematics problem solving. (4) the ability on mathematics problem solving of students with field independent cognitive style who was taught with IDEAL metacognitive instructional strategy is higher than who was taught by KWL and learning portfolio. (5) the ability on mathematics problem solving of students with field dependent cognitive style who was taught with IDEAL and KWL metacognitive instructional strategy is lower than by learning portfolio.